2012
DOI: 10.5754/hge12277
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Platelet Count in Patients with Colorectal Cancer Predicts Tendency to Metastases and Poor Prognosis

Abstract: Elevated platelet might play some role in the progress of CRC and preoperative platelet count might be a prognostic indicator in the CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 0 publications
2
28
1
Order By: Relevance
“…In addition, platelets release PDGF, which is a potent inducer of tumor cell invasion (31). Therefore, high platelet counts were reported to be associated with tumor progression and poor prognosis in numerous types of cancer (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, platelets release PDGF, which is a potent inducer of tumor cell invasion (31). Therefore, high platelet counts were reported to be associated with tumor progression and poor prognosis in numerous types of cancer (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the increased platelet count was associated with poor prognosis in nasopharyngeal carcinoma (Gao et al, 2013), gastric cancer (Hwang et al, 2012), colorectal cancer (Lin et al, 2012), and endometrial carcinomas (Gorelick et al, 2009). Our study found that the elevated values of platelet-based indices predicted poor survival for HCC patients after resection, which was consistent with the findings in other cancers.…”
Section: Discussionmentioning
confidence: 98%
“…A total of 20 studies (7,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) that met the inclusion criteria were retrieved for analysis in the present study. The selection process of the included studies is presented in Fig.…”
Section: Identification Of Eligible Studiesmentioning
confidence: 99%